Determination of residual alkyl iodides and alkyl bromides as their corresponding alkyl chlorides in drug substances by headspace GC-FID - Brian T. Zielke II (Heliyon)
Primary and secondary alkyl iodides and primary alkyl bromides were quickly and conveniently converted into their corresponding alkyl chlorides via SN2 halide-halide substitution. The resultant alkyl chlorides simultaneously demonstrated increased volatility and stability paired with standard headspace GC-FID methodology. The derivatization was performed on both standard and sample alike and occurred during the headspace oven equilibration phase, eliminating the extra reaction step traditionally performed during many derivatization analyses. Reaction times, temperatures, and completeness of conversion were studied as well as response from common headspace solvents and application of various chloride sources. Recovery of iodomethane from four challenging substrates was studied from the trace level to approximately 1000 ppm. Recovery ranged 94–110 % from verapamil hydrochloride (2.5–1007 ppm), 95–102 % from methylnaltrexone bromide (26–1054 ppm), and 92–106 % from (S)-laudanosine (49–942 ppm). Using hydrogen chloride as the chloride source, a method for determination of residual iodomethane in (S)-N-methyl-laudanosine iodide was validated over a 0.5–24.9 μg/mL range with a 0.1 μg/mL detection limit, 91–103 % accuracy, and 3.2 % relative standard deviation.